RESPONSABILIDADE SOCIAL EMPRESARIAL E REDES SOCIAIS NA INTERNET: ESTUDO DE CASO DA EMPRESA SAMARCO - SILVÉRIO, FLÁVIA REGINA MORALES (2018)
The study reflects on the theme of corporate social responsibility as one of the principles of sustainability, establishing a relationship with disaster involving Samarco, which on November 5, 2015 had one of its ruptured ore dams in the region of Mariana , resulting in the dumping of 62 millions of cubic meters of mud, losing biodiversity not only locally, but also throughout the course of the waste. The results of the research on the communicative process of the company with those affected are presented, especially with regard to the use of social networks as a technological facilitator of the dialogue, theoretically underpinning the contemporary subject and its interaction with social networks. As for the methodology used for the development of the work, it is used documentary analysis and content on the case, bibliographic research on the themes: social networks and corporate social responsibility, and finally, a qualitative research with a pre-defined script, applied the relevant actors involved in the issue, with non-probabilistic sampling and accessibility, on a field visit covering the entire mud trail from July 10 to 21, 2017, starting the route in Mariana, passing through Barra Longa (MG), Governador Valadares (MG), Colatina (ES), Linhares and its district: Regência (ES) - where the mouth of the river Doce is located. With the research, it was possible to verify that the process of dialogue between the spokesperson of Samarco, the Renova Foundation, and those affected has occurred, but the major issue is the bureaucracy that involves the solution of the case in relation to the use of technological devices as a facilitator, it has also been used, but in a smaller scale than the face-to-face dialogues.